The association between coeliac disease, dermatitis herpetiformis and certain HLA-antigens in Icelanders - Arnason, A; Skaftadottir, I; Sigmundsson, J; Mooney, E; Bjornsson, J; Cariglia, N; Palsson, G; Gudjonsson, H (European Journal of Immunogenetics, 2011)
To access publisher full text version of this article. Please click on the hyperlink in Additional Links field Twenty-eight cases of coeliac disease (CD) and seven of dermatitis herpetiformis (DH) have been verified in Iceland. Standard serological techniques were used for HLA typing. Twenty-five individuals with CD were typed, 21 (84%) of whom carried DR3,DQ2. Twelve of these 25 (48%) had DR3,DR7, DQ2, which makes them possibly homozygous for DQ2, and suggests that homozygosity of DQ2 increases the risk for CD. The four DH patients that were typed all had HLA-B8,DR3,DQ2. It is concluded that CD and DH are associated with DR3, DQZ in Icelanders.